Hardware-in-the-loop testing of bypass valve actuation system: Design and validation of a simplified real time model. (April 2017) - Pugi, Luca; Galardi, Emanuele; Carcasci, Carlo; Lucchesi, Nicola
During the start-up and shut-down phases of steam power plants many components are subjected to pressure and temperature transients that have to be carefully regulated both for safety and reliability reasons. For this reason, there is a growing interest in the optimization of turbine bypass controllers and actuators which are mainly used to regulate the plant during this kind of operations. In this work, a numerically efficient model for real-time simulation of a steam plant is presented. In particular, a modular Simulink™ library of components such as valves, turbines, and heaters has been developed. In this way, it is possible to easily assemble and customize models able to simulate different plants and operating scenarios. The code, which is implemented for a fixed, discrete step solver, can be easily compiled for a RT target (such as a Texas Instrument DSP) in order to be executed in real time on a low-cost industrial hardware. The proposed model has been used for quite innovative applications such as the development of a hardware-in-the-loop test rig of turbine bypass controllers and valve positioners. Preliminary experimental activities and results of the proposed test rig developed for Velan ABV are introduced and discussed.